Characterization And Environmental Sustainability Assessment Of Groundwater System As An Auxiliary Resource For Paddy Irrigation In Labu Kubong, Teluk Intan, Perak - Akhtar, Naseem (2023)
The challenges facing Malaysia, such as inadequate water management, climate change, drought, and water pollution, are becoming more severe, leading to water stress in isolated paddy plot areas. The study highlights the role of groundwater as an auxiliary resource for paddy irrigation to counteract the alarming trend of the shrinking "rice bowl" area in Labu Kubong. Knowledge of the potential well yield of groundwater resources is critical not only for groundwater resource management purposes but also to determine the significant impact of associated water consumed in groundwater infrastructure and development. Therefore, this study's objectives are: (i) To analyse the geophysical profile of the subsurface area, (ii) To characterize the vertical profiling of soil textures and elemental compositions in the borehole, (iii) To evaluate the transmissivity, hydraulic conductivity and storativity of the aquifer, and (iv) To assess the impact potentials of water consumed associated with the groundwater system. Results showed that the aquifer consists of a sand-silt sequence with an average percentage of 94% and 6%, respectively indicating an alluvial environment with hard rock underlying the Gula Formation. The transmissivity (T), hydraulic conductivity (K), and storativity (S) were evaluated from the series of pumping tests in years 2020 and 2021.